Development of upper air simulator for the calibration of solar radiation effects on radiosonde temperature sensors. (29th November 2019) - Lee, Sang‐Wook; Yang, Inseok; Choi, Byung IL; Kim, Sunghun; Woo, Sang‐Bong; Kang, Woong; Oh, Youn Kyun; Park, Seongchong; Yoo, Jae‐Keun; Kim, Jong Chul; Lee, Young Hee; Kim, Yong‐Gyoo
Abstract: For the accurate measurement of temperature in the upper air by using radiosondes, one prerequisite is the compensation of solar radiation effects that cause sensor heating. The development at the Korea Research Institute of Standards and Science (KRISS) of an upper air simulator (UAS) that can simulate radiation effects is reported. The UAS can independently control four environmental parameters: irradiance, temperature, pressure and air speed. An entire radiosonde can be installed in the test chamber and the measurement data transmitted remotely via an antenna. Solar irradiance is mimicked by using a solar simulator that irradiates the radiosonde sensor. The temperature of the test chamber is controlled from −70 to 20°C by placing it inside a climatic chamber. The pressure and ventilation speed in the test chamber are modulated using combinations of sonic nozzles, a mass flow controller and a vacuum pump. A ventilation speed of 5 m·s −1, which mimics the speed of ascent of the radiosondes when lifted using a balloon, is achieved at pressures as low as 7 hPa. The capability of controlling the environmental parameters independently and the stability of each parameter are presented. As a proof of concept, the radiation‐induced bias on the temperature sensor of a commercial radiosonde Vaisala RS41 is measured. The effect of each parameter is investigated by varying it while keeping the other parameters fixed. Radiosonde calibration using the UAS at the KRISS will help improve the traceability of upper air measurements to the International System of Units. Abstract : The development of an upper air simulator for the calibration of a radiosonde is reported. The simulator can independently control four important climate parameters: temperature, pressure, solar irradiance and ventilation speed. The radiation effect on the air temperature measurement using a commercial radiosonde Vaisala RS41 is assessed at various temperatures and pressures. The temperature rise of the radiosonde sensor due to the irradiation shows temperature dependence at low pressures as well as clear pressure dependence at all temperatures measured.